The Influence of Work Motivation, Leadership Style and Compensation on Employee Performance at Bandung Adventist Hospital - Bara Jonathan Rihi Hina; Mardi Siwoyo; Sediatmoko Sediatmoko; Marisi Pakpahan; Rudianto Rudianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to explore the influence of work motivation, leadership style, and compensation on employee performance at Rumah Sakit Advent Bandung. With a total population of 720 employees, the study uses a simple random sampling technique to select a sample of 88 respondents, deemed sufficiently representative. Data collection is conducted through a Likert-scale questionnaire designed to capture respondents' perceptions of work motivation, leadership style, and compensation variables. To ensure data quality, the instrument's validity is tested through factor analysis, and its reliability is measured using Cronbach’s Alpha to guarantee consistency in results. Hypothesis testing is carried out using classical assumption tests and multiple linear regression analysis via SPSS version 27.The results reveal that work motivation and compensation have a positive and significant impact on employee performance, indicating that higher motivation and compensation are associated with improved employee performance. In contrast, leadership style does not show a significant effect on employee performance, possibly due to varying perceptions of the role of leadership within this organizational context. Collectively, work motivation, leadership style, and compensation variables have a significant effect on employee performance. The obtained R Square value of 0.309 indicates that 30.9% of the variation in employee performance can be explained by these three variables, while the remaining 69.1% is influenced by other factors outside this model, such as work environment, organizational culture, or other individual factors. These findings provide valuable insights for management in designing strategies to enhance employee performance.